Parallel Implementation of A* Search - Mabrouka Algherini (المجلة الأفروآسيوية للبحث العلمي, 2024)
A* algorithm is one of the artificial intelligences searching algorithms that is used to find the shortest rout of path traversal. Executing the algorithm in one processor is not efficient enough for the time of processing therefore rather than execute A * algorithm in one processor, in this paper the algorithm tested in multi processors working together simultaneously to increase the speed up and efficiency of processing time, this work implemented by using Message Passing Interface (MPI) which is work in shared memory and more than one processor. The test is done for a number of cores “1 to 8” and I found that for a greater number of mainframes, the processing time decreased which means fast handling for the calculation.